1996
DOI: 10.1038/bjc.1996.522
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin relates to EGFR expression and lymph node metastasis in primary breast carcinoma

Abstract: showing complete loss of membrane staining, whereas 93% of IDC retained some level of expression. In IDC reactivity was not related to tumour grade but there was a significant association between reduced membrane levels of E-cadherin and the presence of lymph node metastasis, and a highly significant correlation between the presence of cytoplasmic E-cadherin and metastasis. A significant relationship was also demonstrated between reduced E-cadherin reactivity and expression of EGFR. These findings emphasise th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 25 publications
5
47
0
Order By: Relevance
“…In human breast cancer, conflicting results are also to be found in the literature. Thus, significant differences were reported by some authors (Siitonen et al, 1996;Charpin et al, 1997;Gonzalez et al, 1999;Parker et al, 2001;Cobanoglu et al, 2004) but not by others (Jones et al, 1996;Kovacs et al, 2003;Howard et al, 2005). Gamallo et al (1993) demonstrated greater immunoreactivity in grade I carcinomas than in grade II and grade III, giving support to our results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In human breast cancer, conflicting results are also to be found in the literature. Thus, significant differences were reported by some authors (Siitonen et al, 1996;Charpin et al, 1997;Gonzalez et al, 1999;Parker et al, 2001;Cobanoglu et al, 2004) but not by others (Jones et al, 1996;Kovacs et al, 2003;Howard et al, 2005). Gamallo et al (1993) demonstrated greater immunoreactivity in grade I carcinomas than in grade II and grade III, giving support to our results.…”
Section: Discussionsupporting
confidence: 81%
“…In a previous study of canine mammary cancer, five of 41 tumours with confirmed regional lymph node metastasis showed reduced or absent expression of E-cadherin (Restucci et al, 1997). In human breast cancer a significant association between the presence of E-cadherin expression and absence of lymph node metastasis was reported in some (Jones et al, 1996;Hunt et al, 1997;Zschiesche et al, 1997;Madhavan et al, 2001) but not in other studies (Charpin et al, 1997;Burkholm et al, 1998;Gonzalez et al, 1999;Parker et al, 2001;Kovacs et al, 2003). In three studies of human breast cancer, however, it was found that high E-cadherin expression was associated with a larger number of lymph nodes considered positive for metastasis (Siitonen et al, 1996;Gillett et al, 2001;Howard et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…70 -73 Reduced or absent E-cadherin was not significantly related to lymph node status in our series. The clinical significance of E-cadherin expression remains controversial, although it is generally accepted that reduction of E-cadherin expression is associated with invasive growth or axillary lymph node metastasis, 28,30,74,75 However, such a correlation has been explicitly denied in other studies. 27,76 p27 LI and proliferation rate were not statistically related to E-cadherin expression or alterations of 16q22.1 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…IBC therefore constitutes an important exception to the association between loss of E-cadherin expression and increased metastatic potential and poor outcome in breast cancer. Indeed, the E-cadherin-mediated cell adhesion system is known to act as an invasion suppressor system in cancer cells (Vleminckx et al, 1991) and diminished E-cadherin expression has been related to invasiveness, dedifferentiation, lymphovascular invasion, lymph node metastasis, distant metastasis and shortened disease-free survival (Oka et al, 1993;Jones et al, 1996;Siitonen et al, 1996;Asgeirsson et al, 2000;Heimann et al, 2000). The strong E-cadherin expression in IBC, being a highly invasive, poorly differentiated tumour with prominent lymphovascular invasion and high incidence of lymph node and distant metastasis, therefore constitutes a striking difference between IBC and non-IBC.…”
mentioning
confidence: 99%